2020
DOI: 10.1007/s42976-020-00034-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of superior spring durum wheat genotypes under irrigated and rain-fed conditions

Abstract: An important objective of wheat improvement programmes is to breed varieties for high yield in optimum conditions and for minimum yield reduction under stress-prone conditions such as heat and drought. Analyses of yield and its components in multiple years allow a comprehensive and comparative understanding of genetic yield potential and stress-tolerance mechanisms in the study germplasm. The present study was carried out to evaluate performance of elite varieties and landraces of spring durum wheat under diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 26 publications
6
14
0
Order By: Relevance
“…De Vita et al [5] worked on a set of Italian durum wheat genotypes with Rht genes released from 1975 to 2003 and highlighted that "Tiziana" and "Giusto" developed in 2001 have high-yield stability across the tested environments. In agreement with previous studies [13,43,50,52,58,59], our results indicate that modern durum wheat varieties were more responsive to changes in seasons and treatments. In fact, the most stable varieties would not necessarily give the best grain yield [60]; therefore, stability per se should not be the only selection parameter.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…De Vita et al [5] worked on a set of Italian durum wheat genotypes with Rht genes released from 1975 to 2003 and highlighted that "Tiziana" and "Giusto" developed in 2001 have high-yield stability across the tested environments. In agreement with previous studies [13,43,50,52,58,59], our results indicate that modern durum wheat varieties were more responsive to changes in seasons and treatments. In fact, the most stable varieties would not necessarily give the best grain yield [60]; therefore, stability per se should not be the only selection parameter.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, Ercoli et al [47] found that the increase in grain yield was due to a higher number of spikes and greater spike size and suggested that good growing conditions during the initial stages of crop development favored the development of tillers and promoted the floret fecundation. A significant correlation between grain yield and kernel weight was found under rainfed conditions, but not under irrigated ones, which is consistent with previous studies [26,[48][49][50] which reported that kernel weight influences grain production mostly in rainfed areas. Similarly, Bányai et al [50] found that thousand-kernel weight proved a high repeatability under drought stress during the three years of the experiment.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The reactions of plants to drought and high temperature stress are often species-specific, but there are also large differences among cultivars within a species [ 5 , 31 , 37 , 39 , 46 ]. We also found large variations among the 51 wheat cultivars included in this experiment not only in their grain yielding abilities under control conditions but also in their sensitivities to the various heat stress treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The method for assessing the ecological plasticity and variance of its stability of varieties based on the analysis of variance and regression makes it possible to assess their reactions under different growing conditions [12,13].…”
Section: Introductionmentioning
confidence: 99%